Synthesis of C-2 methylene glycosides from C-2 propargyloxymethyl glycals exploiting the alkynophilicity of AuCl3 - Kashyap, Sudhir; Vidadala, Srinivasa Rao; Hotha, Srinivas (Tetrahedron Letters, 2007)
C-2 Methylene glycosides were synthesized from C-2 propargyloxymethyl glycals in a stereoselective manner using a catalytic quantity of AuCl3. The Au-catalyzed reaction was explored using various aglycones. The current protocol enables the preparation of C-2 methylene glycosides, tolerates diverse functional groups and is fast, catalytic and mild. (c) 2007 Elsevier Ltd. All rights reserved.
21st Carbo Symposium 2006, Univ Delhi, Delhi, INDIA, NOV 26-29, 2006

Methyl glycosides are identified as glycosyl donors for the synthesis of glycosides, disaccharides and oligosaccharides - Vidadala, Srinivasa Rao; Hotha, Srinivas (Chemical Communications, 2009)
Stable methyl glycosides are identified as glycosyl donors in the presence of AuBr(3) in acetonitrile; a panel of aglycones comprising aliphatic, alicyclic, steroidal and sugar alcohols are examined successfully for the glycosylation reaction and methyl glycosides of di- and tri-saccharides are converted to corresponding tri- and tetra-saccharides exploiting salient features of our novel activation protocol.

Orthogonal activation of propargyl and n-pentenyl glycosides and 1,2-orthoesters - Vidadala, Srinivasa Rao; Thadke, Shivaji A.; Hotha, Srinivas (Journal of Organic Chemistry, 2009)
An orthogonal activation strategy with propargyl and n-pentenyl glycosides has been identified. According to this methodology, n-pentenyl glycosides can be selectively activated with NIS/TMSOTf in the presence of either armed or disarmed propargyl O-glycosides. In addition, we report herein that propargyl 1,2-orthoesters can be selectively activated with AuBr(3) in CH(2)Cl(2) at room temperature in the presence of n-pentenyl glycosides. Similarly, pentenyl 1,2-orthoesters can be selectively activated with NIS/Yb(OTf)(3) in the presence of propargyl glycosides.

Propargyl/methyl furanosides as potential glycosyl donors - Vidadala, Srinivasa Rao; Gayatri, Gaddamannugu; Sastry, G. Narahari; Hotha, Srinivas (Chemical Communications, 2011)
Transfuranosylations are not well studied though many similar studies exist for transpyranosylation; herein, we report that propargyl/methyl D-ribf- and D-lyxf- give only 1,2-trans glycosides whereas D-araf- and D-xylf- result in a mixture of 1,2-trans and 1,2-cis glycosides; observed facts are rationalised by computational studies.